A implementação de Smart Cities no Brasil e no mundo - LIMA, Marcos Rodrigo Souza de (2024)
In today's world there are several Smart Cities implementation projects, where this new concept appears to make use of new technologies, therefore, it exists to meet social and market demands. As a theoretical review, an introductory section is presented on the development of cities through the technologies presented, in view of the evolution and implementation of the mobile network with a focus on the current 5G technology being used for this purpose.